1983
DOI: 10.1177/036354658301100415
|View full text |Cite
|
Sign up to set email alerts
|

Impacted third molars: A contributing factor in mandibular fractures in contact sports

Abstract: Studies have shown that the presence of impacted third molars places the mandible at increased risk for fracture. Individuals participating in high contact sports are subject to maxillofacial trauma; therefore, participants with impacted third molars are at increased risk for fractured mandibles. Three cases are reviewed to illustrate this problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…Based on this evidence, some investigators have advocated removing unerupted mandibular third molars to prevent mandibular angle fractures 5,13,17 . However, we have often observed that patients without unerupted mandibular third molars were more likely to have a condyle fracture than those with unerupted mandibular third molars.…”
mentioning
confidence: 99%
“…Based on this evidence, some investigators have advocated removing unerupted mandibular third molars to prevent mandibular angle fractures 5,13,17 . However, we have often observed that patients without unerupted mandibular third molars were more likely to have a condyle fracture than those with unerupted mandibular third molars.…”
mentioning
confidence: 99%
“…Traumatic impacts of low intensity resulting in energy distribution along the lesioned body are suggested to be more frequently associated with mandibular angle fractures, especially when a third molar is involved. Physical aggressions and sportsrelated injuries are the main examples of this type of etiological agent (4,5,(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…No literature reviews (14), mechanical assays with computer simulation (15), or metaanalyses (11) presenting a type of study or approach different from that evaluated in the present study (2,(16)(17)(18)(19)(20) and that did not define angle fracture (21) were selected. Among the articles selected, those presenting some type of sample limitation, for example, including a specific group of individuals (22,23), those not differentiating between erupted and absent third molars (24), and those including samples previously used in other studies (9,10,25) were excluded, with only studies remaining that clearly reported the data of the sample (8). After exclusion, five articles (3)(4)(5)(6)8), which possessed a similar methodology that permitted the comparison of their data, continued in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Mandibular fractures follow a pattern, common to many injuries, in that young males are predominantly affected (2) The reported rate of occurrence of mandibular fractures is 11.5 per 100,000 people per year (3).Many investigators have reported that patients with unerupted mandibular third molars were more likely to have an angle fracture than those patients without unerupted mandibular third molars. This has been attributed to the decreased cross-sectional area of bone at the mandibular angle that contains the unerupted third molars(4-6).…”
Section: Imentioning
confidence: 99%